Rational Evaluation and Treatment of Prolactinomas: A Concise Review - Mahzari, Moeber M. (Journal of Diabetes and Endocrine Practice, 2022)
Prolactinoma is the most common pituitary tumor. It arises from the lactotroph cells and leads to a hyperprolactinemia state. The clinical presentation of prolactinomas is either due to the high prolactin state or the adenoma mass effect. Diagnosis of prolactinomas starts with the confirmation of persistent pathologic hyperprolactinemia. Subsequently, pituitary MRI is required to characterize the prolactinoma size and extension within the sella turcica. Further investigation may include visual field assessment and laboratory investigations for hypopituitarism. Prolactinoma management is mainly medical with dopamine agonists as most of these tumors are responsive. Surgical intervention is rarely required with specific indications.
Keywords: prolactinoma; hyperprolactinemia; dopamine agonist; pregnancy